2022
DOI: 10.21037/atm-22-397
|View full text |Cite
|
Sign up to set email alerts
|

How long does it take to translate research findings into routine healthcare practice?—the case of biological drugs for rheumatoid arthritis in Brazil

Abstract: Background The literature reports long time lags between the several processes involved in the translation of drug research and development into clinical application. To expedite these processes, translational research has emerged as a process that can be applied to reduce the lag between scientific discoveries and their practical application. Thus, the objective of this study was to estimate the time lag in translational research of biological drugs for the treatment of rheumatoid arthritis inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Despite the advancements and enhanced knowledge gained from innovative research, the translation of these into therapeutic benefits has not been fully realised. A study in Brazil found the average time lag from the clinical development to the application of biological drugs was 11.3 years [48]. Upadacitinib is the most recent treatment approved for RA with clinical trials to determine safety and efficacy in 2015 and approved for use in the UK in April 2021 [49].…”
Section: Limitations Of Current Guidelinesmentioning
confidence: 99%
“…Despite the advancements and enhanced knowledge gained from innovative research, the translation of these into therapeutic benefits has not been fully realised. A study in Brazil found the average time lag from the clinical development to the application of biological drugs was 11.3 years [48]. Upadacitinib is the most recent treatment approved for RA with clinical trials to determine safety and efficacy in 2015 and approved for use in the UK in April 2021 [49].…”
Section: Limitations Of Current Guidelinesmentioning
confidence: 99%
“… 15 The Brazilian Unified Health System (SUS) is responsible for the provision of healthcare and pharmaceutical assistance to over 200 million people. 16 Therefore, the Brazilian SUS constitutes a privileged scenario for pharmacovigilance. 17 The national protocol regarding the sequence of medications used in psoriasis is not different from most international recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The process of inclusion, alteration, and exclusion of health technologies, focused mainly on hard technologies such as medicines, procedures, and medical materials, adopts well-defined criteria and an organized flow to analyze internal and external demands on the SUS 9 , linked to a transparent administrative process with well-defined deadlines, consolidated from 2011 9,11 . In contrast to a welldefined evaluation stage 9 that includes significant investments in innovative technologies 12 , implementing incorporated technologies, that is, their effective use in clinical practice, is still a challenge in Brazil 13,14 . Although the PNGTS publication and Law No.…”
Section: Introductionmentioning
confidence: 99%